(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Colposcopy is a good diagnostic tools for the detection of abnormalities cervix of the uterus. Objective: The purpose of the present study was to see the histological diagnosis of colposcopically negative cases for CIN among VIA positive women. Methodology: This cross sectional study was conducted in the Department Of Pathology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh during the period of July 2007 to June 2008 for one (01) year. Patients who are colposcopically negative but clinically suspicious for cervical neoplasia were included in this study. The cervix was examined on naked eye by Cusco’s speculum to see whether it was healthy or not. Then it was examined by the colposcope after applying 3 to 5% acetic acid and colposcopic findings were collected. VIA positive cases were underwent colposcopy guided LEEP biopsy. Result: A total of 63 patients of different age group were recruited for this study. The age of 63 patients ranged from 20 years to 65 years with an average age of 34.6±9.59 years. Among 63 VIA positive patients, 54 cases were colposcopically positive for cervical intraepithelial neoplasia and carcinoma in situ, remaining 9 patients were colposcopically negative. Histological examination was also performed in nine patients who were colposcopically negative but clinically suspicious for malignancy or precancerous lesion. Of these nine cases, eight cases (89%) were diagnosed as chronic cervicitis, one case (11.0%) as CIN-I and none as CIN-II and CIN- III. Conclusion: In conclusion majority of the colposcopically negative VIA positive cases are the patients of chronic cervicitis. Journal of National Institute of Neurosciences Bangladesh, 2020;6(1): 29-32